Literature and Painting In Quebec : From Imagery to Identity - Berg, William J. (Book collections on Project MUSE., 2012)
This unique study explores how Quebec's landscapes have been represented in both literature and visual art throughout the centuries, from the writing of early explorers such as Cartier and Champlain to work by prominent contemporary authors and artists from the province. William J. Berg traces recurrent images and themes within these creations through the most significant periods in the development of a Quebecois identity that was threatened initially by the wilderness and indigenous populations, and later by the dominance of British and American influences.Focusing on the interplay between nature and culture in landscape representation, Literature and Painting in Quebec contends that both have reflected and fashioned the meaning of French-Canadian nationhood. As such, Literature and Painting in Quebec presents a new perspective to approach the notion of national identity, a quest that few groups have engaged in more persistently than the Quebecois.